A predictor of outcome following head injury: A retrospective study - Agnes Silvina Marbun; Elida Sinuraya; Amila Amila; Galvani Volta Simanjuntak (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2021)
Background: Head injuries are a major cause of death and disability because of trauma, it happed in many countries of the world. The case of head injuries in the Emergency department, need immediate managing to victim to prevent further complications. The Nurses required to assess and recognize abnormality as soon as possible and further management of the victim to save their life. Through the physiological status. The patient's physiological status is the best way to recognize the prognosis, such as GCS, systolic blood pressure, respiratory rate, body temperature, and blood glucose levels while admitted to emergency ward.Purpose: To analyze and determine (simultaneously) a predicting factor the most dominant influencing significantly of outcome following head injuryMethods: A retrospective approach by analyze patient's medical records on January-December period in 2018 at H. Adam Malik General Hospital Medan. The study sample comprised 166 medical records which taken by purposive sampling technique with the following criteria: new admission (not referral), there were available data such GCS data, systolic blood pressure, respiratory rate, body temperature, blood glucose levels within 7 days under treatment.Results: Logistic regression test found that GSC (p 0.000; OR 2.583), systolic blood pressure (p 0.024; OR 0.947), and blood sugar levels (0.038; OR 0.982) had a significant effect on the mortality. The nurse must pay attention in handling patient head injuries who have a lower GCS scores and systolic blood pressure, following by high blood sugar levels.Conclusion: By evaluation of GCS, systolic blood pressure and blood sugar levels can predict the patient's current condition. The lower the GCS score, the higher the risk of death by 2.583 times and the lower the systolic blood pressure, the greater the risk of mortality by 0.947 times. The higher the blood sugar level, the risk of death increased by 0.982 times.